New Clinical and Morphologic Aspects in Trigeminal Neuralgia - Tanrikulu, Levent; Hastreiter, Peter; Bassemir, Teresa; Bischoff, Barbara; Buchfelder, Michael; Dörfler, Arnd; Naraghi, Ramin (World Neurosurgery, 2016)
OBJECTIVE: High-resolution magnetic resonance imaging can be used to delineate the morphology of neurovascular compression (NVC) in detail. This study focuses on essential morphologic parameters in relation to the clinical appearance of patients with trigeminal neuralgia (TN). METHODS: A total of 180 patients with TN underwent magnetic resonance-constructive interference in steady state/time of flight. Parameters of the affected nerves (length) and causative vessels were examined: (1) the relationship between the NVC site (caudal/cranial/laterocaudal/mediocranial) and affected area (V1, V2, V3); (2) nerve deformity; (3) vascular loop; (4) existence of a "cerebrospinal fluid (CSF) sign" by a separation of trigeminal fascicles by a vessel; and (5) localization of the causative vessel. RESULTS: A total of 10 patients with V1 affection showed 6 caudal, 0 cranial and laterocaudal, and 4 mediocranial NVC; 26 patients with V2 affection showed 17 caudal, 0 cranial, 1 laterocaudal, and 8 mediocranial NVC; 29 patients with V3 affection showed 23 caudal, 1 cranial, 3 laterocaudal, and 2 mediocranial NVC; 25 patients with V1 and V2 affection showed 17 caudal, 1 cranial, 0 laterocaudal, and 7 mediocranial NVC; 36 patients with V2 and V3 affection showed 30 caudal, 3 cranial, 1 laterocaudal, and 2 mediocranial NVC; and 6 patients with V1, V2, and V3 affection showed 4 caudal, 1 cranial, 0 laterocaudal, and 1 mediocranial NVC. A total of 63 patients (35%) showed nerval deformity by distorsion of the trigeminal fascicles from compressing vessel; 37 of 39 patients (95%) with right-sided deformity showed right-sided TN; and 21 of 22 patients (95%) with left-sided TN showed left-sided nerve deformation. Two patients with bilateral nerve deformity showed bilateral TN. Rostral superior cerebellar artery (SCA) loop compression was seen in 24 patients (17%), caudal SCA loop compression was seen in 10 patients (7%), and double SCA loop compression was seen in 33 patients (23%). Sandwich compression was seen in 18 (12%), and a CSF sign was seen in 24 patients. All 24 patients (100%) with a CSF sign had V1 affection. CONCLUSIONS: The CSF sign is pathognomonic for V1 affection. Vascular loops from cranial on the nerve were the most frequent types of compression in all areas of pain, followed by mediocranial loops. This evaluation is reproducible and contributes to the role of magnetic resonance imaging and a classification of findings in the preoperative evaluation of NVC.
EVALuna2:33152